A high entropy hydrotalcite-modified carbon fiber photothermal conversion material and preparation method thereof
By using waste fabrics to prepare porous carbon fibers and uniformly coat high-entropy hydrotalcite on its surface, the problems of long production cycle, complex process and high cost of existing photothermal conversion materials are solved, and efficient photothermal conversion and water evaporation effects are achieved.
Patent Information
- Application Number
- CN202310233370.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-03-13
AI Technical Summary
The low energy conversion rate of existing solar distillation devices limits the practical application of solar energy in the field of water treatment. In addition, the existing photothermal conversion materials have a long production cycle, complex process, high cost, and are difficult to produce on a large scale, poor water absorption capacity, low water evaporation rate and low photothermal conversion efficiency.
Use waste fabric as raw material to obtain porous carbon fibers through heat treatment and process them in a nitrogen or argon atmosphere. Then, the metal salt is prepared in an equimolar ratio to form a mixed salt melt and impregnate the carbon fibers to prepare a high-entropy hydrotalcite modified carbon fiber photothermal conversion material.
It achieves large-scale production with short production cycle, simple process, low cost, and cheap raw materials. The materials have excellent photothermal conversion efficiency and high water evaporation rate.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon fiber photothermal conversion materials, and specifically relates to a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material and a preparation method thereof. Background Art
[0002] Although there are abundant water resources on the earth, seawater accounts for 96.5% of the total water on the earth, while drinking fresh water accounts for only about 2.5% of the total water on the earth. With the continuous growth of population and rapid economic development, the shortage of fresh water resources has become more prominent. Convenient, cheap and efficient access to fresh water resources is the direction of researchers' efforts. Waste textiles not only cause a lot of waste of resources but also increase environmental pollution. Therefore, making full use of waste fabrics is of great significance to improving resource utilization and protecting the environment.
[0003] Solar energy has become a clean energy that is widely concerned and focused on by countries around the world due to its clean, safe, convenient and efficient characteristics. Using solar energy to obtain pure water from seawater or sewage is a low-carbon green technology for obtaining fresh water resources. Existing solar distillation devices can use solar energy to heat water for evaporation and then condense to obtain clean water resources, but their energy conversion rate is low (<30%), which greatly limits the practical application of solar energy in the field of water treatment.
[0004] Although the photothermal conversion material prepared by the patent "A carbon nanofiber film photothermal conversion material and its preparation" (CN103361625A) has improved light absorption rate and heat exchange efficiency, the metal matrix pretreatment process selected in the patent is time-consuming and costly, making it difficult to apply in large-scale production; although the photothermal conversion material prepared by the patent "Carbon fiber photothermal conversion material and its use in purification and recovery of multi-medium solvents" (CN111249757A) has high solar energy conversion efficiency, the preparation process of the carbon fiber photothermal conversion material described in the patent is complicated, and the specific surface area and surface roughness of the hydrothermal carbon layer are difficult to control, thereby affecting the photothermal conversion efficiency; the composite carbon fiber material prepared by the patent "A photothermal conversion composite nanocarbon fiber membrane and its preparation method" (CN113699686A) absorbs sunlight through multiple refractions, thereby improving light absorption, but the hot pressing treatment described in the patent can easily destroy the pores of the fiber film, affecting the water absorption capacity of the composite material, thereby affecting the water evaporation efficiency of the composite carbon fiber material.
[0005] In summary, the prior art has the following technical defects: long production cycle, complex process, low cost, and difficulty in large-scale production; the prepared photothermal conversion material has poor water absorption capacity, low water evaporation rate and low photothermal conversion efficiency. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiencies of the above-mentioned existing materials and technologies, and to provide a method for preparing a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material with a short production cycle, simple process, low cost, cheap and readily available raw materials, and the ability to achieve large-scale production. The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material prepared by this method has excellent photothermal conversion efficiency and high water evaporation rate.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] (1) In a nitrogen or argon atmosphere, the waste fabric is heat treated at a temperature of 300 to 700° C. for 120 to 300 minutes to obtain a carbon fiber with a porous structure.
[0009] (2) The metal salts are mixed in an equal molar ratio and stirred at 100 to 200° C. for 10 to 25 minutes to obtain a mixed salt melt; the carbon fiber with a porous structure is immersed in the mixed salt melt for 10 to 30 minutes, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material.
[0010] The high-entropy hydrotalcite-modified carbon fiber light-to-heat conversion material has a porous structure, and the high-entropy hydrotalcite is uniformly coated on the surface of the carbon fiber with the porous structure.
[0011] In the above technical solution:
[0012] The waste fabric is one or more of waste natural plant fiber textiles, waste high polymer synthetic fiber textiles and waste mixed fiber textiles.
[0013] The metal salt is any 5 to 10 of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, manganese chloride monohydrate, ferric nitrate nonahydrate, ferric chloride hexahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, iridium trichloride hydrate, ruthenium trichloride hydrate, and rhodium trichloride hydrate.
[0014] Due to the adoption of the above technical solution, the present invention has the following positive effects and outstanding features compared with the prior art:
[0015] (1) The waste fabric of the present invention is a renewable waste material in the textile industry, which has the characteristics of high purity, large aspect ratio, excellent mechanical properties, etc., and belongs to the recycling of waste. The waste fabric is a flat soft piece composed of small and soft objects through crossing, entanglement and connection. It has a rich and orderly pore structure. Its material is mostly cotton fiber (cellulose content is greater than 90%), polyester fiber, acrylic fiber and other long-chain polymer compounds. After carbonization treatment, the volume shrinkage is small, and the obtained carbon fiber basically maintains the one-dimensional fiber shape and the porous structure of the fabric, which can effectively retain the porous structure of the carbon fiber, has strong water absorption capacity, and high light-to-heat conversion efficiency.
[0016] (2) The source of waste fabric raw materials is very wide and low-priced. The carbon fiber obtained by pyrolysis is amorphous carbon with a low degree of graphitization. It has a large number of defects and hydrophilic functional groups on the surface and has good wettability with water. It can effectively increase the interfacial water content, which is beneficial to the nucleation and growth of high-entropy hydrotalcite on its surface, promote the coating of high-entropy hydrotalcite on the surface of uniform porous carbon fiber, and effectively improve the photothermal conversion efficiency of carbon fiber materials.
[0017] (3) The present invention uses metal nitrates or chlorides containing crystal water as raw materials. Metal nitrates and chlorides have relatively low melting points. Mixing different metal salts can further reduce the melting point, ensuring that a uniform mixed salt melt is formed at a relatively low temperature. The metal cations in the mixed molten salt combine with the hydroxyl groups in the crystal water to form a high-entropy hydrotalcite with uniform distribution of metal elements. The preparation method is simple in process, does not require additional heat treatment and high-temperature and high-pressure equipment, has a short production cycle, and has low production costs.
[0018] (4) The present invention uses waste fabric pyrolysis carbon fiber as a carrier, and then loads high entropy hydrotalcite through a simple impregnation process. During the preparation process, by adjusting the type of metal ions, the semiconductor band gap structure can be effectively regulated, the material's absorption rate and utilization rate of sunlight can be enhanced, and the photothermal conversion efficiency of high entropy hydrotalcite-modified carbon fiber photothermal conversion materials can be significantly improved.
[0019] (5) The high entropy hydrotalcite of the present invention is a layered multi-metal composite hydroxide with abundant hydrophilic functional groups and a large number of microporous structures, as well as a large specific surface area and strong adsorption capacity. When combined with porous carbon fibers, it can provide a rich microporous structure for the carbon fiber matrix, increase the transmission and diffusion channels of water molecules, thereby improving the hydrophilicity of the material surface and the water molecule transport capacity, thereby greatly improving the water evaporation rate of the carbon fiber photothermal conversion material. In addition, the NO of the anions between the hydrotalcite layers 3- It is easily replaced by anions in the wastewater, thereby achieving the purpose of removing pollutants.
[0020] Therefore, the present invention has a short production cycle, a simple process, low cost, cheap and readily available raw materials, and can achieve large-scale production. The prepared high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has excellent photothermal conversion efficiency and high water evaporation rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XRD diagrams of 1 to 4 high entropy hydrotalcite-modified carbon fiber photothermal conversion materials prepared by the present invention;
[0022] Figure 2 for Figure 1 SEM image of the fourth high entropy hydrotalcite-modified carbon fiber photothermal conversion material;
[0023] Figure 3 for Figure 1 EDS image of the fourth high entropy hydrotalcite-modified carbon fiber photothermal conversion material;
[0024] Figure 4 for Figure 1 The photothermal conversion temperature diagram of the first high entropy hydrotalcite-modified carbon fiber photothermal conversion material under different light intensities;
[0025] Figure 5 for Figure 1 Evaporation rates of the first, second and fourth high entropy hydrotalcite-modified carbon fiber photothermal conversion materials. DETAILED DESCRIPTION
[0026] The present invention is described comprehensively and in detail below in conjunction with the accompanying drawings and screenshot implementation methods, but the protection scope of the present invention is not limited to the following specific implementation methods.
[0027] A high entropy hydrotalcite-modified carbon fiber photothermal conversion material and a preparation method thereof. The preparation method described in this specific embodiment is:
[0028] (1) In a nitrogen or argon atmosphere, the waste fabric is heat treated at a temperature of 300 to 700° C. for 120 to 300 minutes to obtain a carbon fiber with a porous structure.
[0029] (2) The metal salts are mixed in an equal molar ratio and stirred at 100 to 200° C. for 10 to 25 minutes to obtain a mixed salt melt; the carbon fiber with a porous structure is immersed in the mixed salt melt for 10 to 30 minutes, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material.
[0030] The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has a porous structure, the high-entropy hydrotalcite is evenly coated on the surface of the carbon fiber with the porous structure, and the metal elements in the metal salt are evenly distributed on the surface of the carbon fiber.
[0031] In the above technical solution:
[0032] The waste fabric is one or more of waste natural plant fiber textiles, waste high polymer synthetic fiber textiles and waste mixed fiber textiles.
[0033] The metal salt is any 5 to 10 of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, manganese chloride monohydrate, ferric nitrate nonahydrate, ferric chloride hexahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, iridium trichloride hydrate, ruthenium trichloride hydrate, and rhodium trichloride hydrate.
[0034] Example 1
[0035] A high entropy hydrotalcite-modified carbon fiber photothermal conversion material and a preparation method thereof. The preparation method described in this embodiment is:
[0036] (1) In an argon atmosphere, the waste fabric was heat treated at 700°C for 300 min to obtain a carbon fiber with a porous structure.
[0037] (2) The metal salts are mixed in an equal molar ratio and stirred at 100° C. for 10 minutes to obtain a mixed salt melt; the carbon fiber with a porous structure is immersed in the mixed salt melt for 10 minutes, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material.
[0038] The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has a porous structure, the high-entropy hydrotalcite is evenly coated on the surface of the carbon fiber with the porous structure, and the metal elements in the metal salt are evenly distributed on the surface of the carbon fiber.
[0039] In this embodiment:
[0040] The waste fabrics are waste natural plant fiber textiles.
[0041] The metal salts are five kinds of metal salts: aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate and nickel nitrate hexahydrate.
[0042] Example 2
[0043] A high entropy hydrotalcite-modified carbon fiber photothermal conversion material and a preparation method thereof. The preparation method described in this embodiment is:
[0044] (1) In an argon atmosphere, the waste fabric was heat treated at 600°C for 250 min to obtain a carbon fiber with a porous structure.
[0045] (2) The metal salts are mixed in an equimolar ratio and stirred at 130° C. for 15 minutes to obtain a mixed salt melt; the carbon fiber with a porous structure is immersed in the mixed salt melt for 15 minutes, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material.
[0046] The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has a porous structure, the high-entropy hydrotalcite is evenly coated on the surface of the carbon fiber with the porous structure, and the metal elements in the metal salt are evenly distributed on the surface of the carbon fiber.
[0047] In this embodiment:
[0048] The waste fabric is waste high polymer synthetic fiber textile.
[0049] The metal salts are 8 kinds of metal salts, namely, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate and zinc nitrate hexahydrate.
[0050] Example 3
[0051] A high entropy hydrotalcite-modified carbon fiber photothermal conversion material and a preparation method thereof. The preparation method described in this embodiment is:
[0052] (1) In a nitrogen atmosphere, the waste fabric was heat treated at 500°C for 150 min to obtain a carbon fiber with a porous structure.
[0053] (2) The metal salts are mixed in an equal molar ratio and stirred at 150° C. for 20 minutes to obtain a mixed salt melt; the carbon fiber with a porous structure is immersed in the mixed salt melt for 20 minutes, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material.
[0054] The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has a porous structure, the high-entropy hydrotalcite is evenly coated on the surface of the carbon fiber with the porous structure, and the metal elements in the metal salt are evenly distributed on the surface of the carbon fiber.
[0055] In this embodiment:
[0056] The waste fabrics are waste mixed fiber textiles.
[0057] The metal salts are 9 kinds of metal salts, namely, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate and hydrated rhodium trichloride.
[0058] Example 4
[0059] A high entropy hydrotalcite-modified carbon fiber photothermal conversion material and a preparation method thereof. The preparation method described in this embodiment is:
[0060] (1) In an argon atmosphere, the waste fabric was heat treated at 400°C for 120 min to obtain a carbon fiber with a porous structure.
[0061] (2) The metal salts are prepared in an equimolar ratio and stirred at 180° C. for 23 minutes to obtain a mixed salt melt; the carbon fiber with a porous structure is immersed in the mixed salt melt for 25 minutes, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material.
[0062] The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has a porous structure, the high-entropy hydrotalcite is evenly coated on the surface of the carbon fiber with the porous structure, and the metal elements in the metal salt are evenly distributed on the surface of the carbon fiber.
[0063] In this embodiment:
[0064] The waste fabric is a mixture of waste natural plant fiber textiles and waste high polymer synthetic fiber textiles.
[0065] The metal salts are six kinds of metal salts: magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate and copper nitrate trihydrate.
[0066] Example 5
[0067] A high entropy hydrotalcite-modified carbon fiber photothermal conversion material and a preparation method thereof. The preparation method described in this embodiment is:
[0068] (1) In an argon atmosphere, the waste fabric was heat treated at 300°C for 180 min to obtain a carbon fiber with a porous structure.
[0069] (2) The metal salts are prepared in an equal molar ratio and stirred at 200° C. for 25 minutes to obtain a mixed salt melt; the carbon fiber with a porous structure is immersed in the mixed salt melt for 30 minutes, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material.
[0070] The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has a porous structure, the high-entropy hydrotalcite is evenly coated on the surface of the carbon fiber with the porous structure, and the metal elements in the metal salt are evenly distributed on the surface of the carbon fiber.
[0071] In this embodiment:
[0072] The waste fabric is a mixture of waste natural plant fiber textiles, waste high polymer synthetic fiber textiles and waste mixed fiber textiles.
[0073] The metal salts are 9 kinds of metal salts: aluminum nitrate nonahydrate, manganese chloride monohydrate, ferric chloride hexahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, zinc nitrate hexahydrate, iridium chloride hydrate, ruthenium chloride hydrate and rhodium chloride hydrate.
[0074] Compared with the prior art, this specific implementation has the following positive effects and outstanding features:
[0075] (1) The waste fabric of the present invention is a renewable waste material in the textile industry, which has the characteristics of high purity, large aspect ratio, excellent mechanical properties, etc., and belongs to the recycling of waste. The waste fabric is a flat soft piece composed of small and soft objects through crossing, entanglement and connection. It has a rich and orderly pore structure. Its material is mostly cotton fiber (cellulose content is greater than 90%), polyester fiber, acrylic fiber and other long-chain polymer compounds. After carbonization treatment, the volume shrinkage is small, and the obtained carbon fiber basically maintains the one-dimensional fiber shape and the porous structure of the fabric, which can effectively retain the porous structure of the carbon fiber, has strong water absorption capacity, and high light-to-heat conversion efficiency.
[0076] (2) The source of waste fabric raw materials is very wide and low-priced. The carbon fiber obtained by pyrolysis is amorphous carbon with a low degree of graphitization. It has a large number of defects and hydrophilic functional groups on the surface and has good wettability with water. It can effectively increase the interfacial water content, which is beneficial to the nucleation and growth of high-entropy hydrotalcite on its surface, promote the coating of high-entropy hydrotalcite on the surface of uniform porous carbon fiber, and effectively improve the photothermal conversion efficiency of carbon fiber materials.
[0077] (3) The present invention uses metal nitrates or chlorides containing crystal water as raw materials. Metal nitrates and chlorides have relatively low melting points. Mixing different metal salts can further reduce the melting point, ensuring that a uniform mixed salt melt is formed at a relatively low temperature. The metal cations in the mixed molten salt combine with the hydroxyl groups in the crystal water to form a high-entropy hydrotalcite with uniform distribution of metal elements. The preparation method is simple in process, does not require additional heat treatment and high-temperature and high-pressure equipment, has a short production cycle, and has low production costs.
[0078] (4) The present invention uses waste fabric pyrolysis carbon fiber as a carrier, and then loads high entropy hydrotalcite through a simple impregnation process. During the preparation process, by adjusting the type of metal ions, the semiconductor band gap structure can be effectively regulated, the material's absorption rate and utilization rate of sunlight can be enhanced, and the photothermal conversion efficiency of high entropy hydrotalcite-modified carbon fiber photothermal conversion materials can be significantly improved.
[0079] (5) The high entropy hydrotalcite of the present invention is a layered multi-metal composite hydroxide with abundant hydrophilic functional groups and a large number of microporous structures, as well as a large specific surface area and strong adsorption capacity. When combined with porous carbon fibers, it can provide a rich microporous structure for the carbon fiber matrix, increase the transmission and diffusion channels of water molecules, thereby improving the hydrophilicity of the material surface and the water molecule transport capacity, thereby greatly improving the water evaporation rate of the carbon fiber photothermal conversion material. In addition, the NO of the anions between the hydrotalcite layers 3- It is easily replaced by anions in the wastewater, thereby achieving the purpose of removing pollutants.
[0080] The high entropy hydrotalcite-modified carbon fiber photothermal conversion material prepared in this specific embodiment is shown in the accompanying drawings: Figure 1 XRD patterns of 1 to 4 high entropy hydrotalcite-modified carbon fiber photothermal conversion materials prepared in Examples 1 to 4; Figure 2 for Figure 1 SEM image of the fourth high entropy hydrotalcite-modified carbon fiber photothermal conversion material; Figure 3 for Figure 1 EDS of the fourth high entropy hydrotalcite-modified carbon fiber photothermal conversion material; Figure 4 for Figure 1 The photothermal conversion temperature diagram of the first high entropy hydrotalcite-modified carbon fiber photothermal conversion material under different light intensities; Figure 5 for Figure 1 The evaporation rates of the first, second and fourth high entropy hydrotalcite-modified carbon fiber photothermal conversion materials. Figure 1 , Figure 2 and Figure 3 It can be seen that the metal elements of the metal salt used in Example 4 are all attached to the porous carbon fibers. Figure 4 It can be seen that the photothermal conversion temperature of the prepared photothermal conversion material increases with the increase of light intensity; Figure 5 It can be seen that the water evaporation rate of the high-entropy hydrotalcite-modified carbon fiber photothermal conversion materials prepared in the first, second and fourth types is high.
[0081] Therefore, this specific embodiment has a short production cycle, simple process, low cost, cheap and readily available raw materials, and can be mass-produced. The prepared high-entropy hydrotalcite-modified carbon fiber photothermal conversion material has excellent photothermal conversion efficiency and high water evaporation rate.
Claims
1. A method for preparing a high entropy hydrotalcite-modified carbon fiber photothermal conversion material, characterized in that The preparation method is: (1) In a nitrogen or argon atmosphere, the waste fabric is heat treated at a temperature of 300-700°C for 120-300 min to obtain a carbon fiber with a porous structure; (2) The metal salts are prepared in an equal molar ratio, and stirred at 100-200° C. for 10-25 min to obtain a mixed salt melt; the carbon fiber having a porous structure is immersed in the mixed salt melt for 10-30 min, taken out, washed with water, and dried to obtain a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material; The waste fabric is one or more of waste natural plant fiber textiles, waste polymer synthetic fiber textiles and waste mixed fiber textiles; The metal salt is any 5 to 10 of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, manganese chloride monohydrate, ferric nitrate nonahydrate, ferric chloride hexahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, iridium trichloride hydrate, ruthenium trichloride hydrate, and rhodium trichloride hydrate.
2. A high entropy hydrotalcite-modified carbon fiber photothermal conversion material, characterized in that The high-entropy hydrotalcite-modified carbon fiber photothermal conversion material is a high-entropy hydrotalcite-modified carbon fiber photothermal conversion material prepared according to the preparation method of the high-entropy hydrotalcite-modified carbon fiber photothermal conversion material according to claim 1; The high-entropy hydrotalcite-modified carbon fiber light-to-heat conversion material has a porous structure, and the high-entropy hydrotalcite is uniformly coated on the surface of the carbon fiber with the porous structure.
Citation Information
Patent Citations
Carbon nanofiber membrane photo-thermal converting material and preparation method thereof
CN103361625A
Carbon fiber photo-thermal conversion material and application in purifying and recovering of multi-medium solvent
CN111249757A
Photo-thermal conversion composite carbon nanofiber film and preparation method thereof
CN113699686A
Preparation method for absorbing mixed fused salt carbon felt electrodes
CN103116046A
Rare earth oxide modified silicon carbide ceramic based composite material and preparation method thereof
CN110407597A